Analyse von Alterungsmechanismen im Hinblick auf die Effizienz von Haushaltskältegeräten - Paul, Andreas
Die Energieaufnahme von Haushaltskältegeräten ist seit den 1990er Jahren erheblich gesunken. Dieser Wert wird von den Herstellern im Neuzustand der Geräte unter Normbedingungen bestimmt. Wie jedes technische System unterliegen jedoch auch Haushaltskältegeräte einem Alterungsprozess, der zu einem Anstieg der Energieaufnahme über die Zeit führt. Im Rahmen dieser Dissertation wurde auf der Grundlage von 100 Messungen der Energieaufnahme, die an 32 Geräten über einen Zeitraum von 21 Jahren durchgeführt wurden, ein Alterungsmodell entwickelt. Dieses Modell ist das erste, das mit Hilfe von Daten der Energieaufnahme real gealterter Geräte entwickelt wurde. Es beschreibt einen Anstieg der Energieaufnahme von 27 % über die durchschnittliche Einsatzzeit eines Haushaltskältegeräts von 16 Jahren. Der stärkste Anstieg erfolgt in den ersten fünf Betriebsjahren. Durch Diffusionsvorgänge in dem im Gehäuse verbauten Polyurethan-Schaum wird das im Zellgas vorhandene Kohlenstoffdioxid durch Luft ersetzt. Hierdurch steigt die Wärmeleitfähigkeit des Schaums um ca. 33 % an, wodurch sich die Energieaufnahme der Geräte erhöht. Des Weiteren wurde der Einsatz von Paraffinen als Phasenwechselmaterial in Haushaltskältegeräten untersucht. Durch deren Einsatz konnte die Energieaufnahme gesenkt und die Funktionalität der Geräte gesteigert werden. Hierfür sind detaillierte Kenntnisse der Materialkenndaten der Paraffine notwendig. Die Wärmeleitfähigkeit der verschiedenen Paraffin-Stoffgruppen in der festen Phase ist jedoch bisher nur unzureichend untersucht worden. Daher wurde ein Messaufbau entwickelt, mit dem die Wärmeleitfähigkeit von festem Paraffin bestimmt werden kann, und es wurden entsprechende Messungen durchgeführt.

Impact of aging on the energy efficiency of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Becker, Wolfgang; Vrabec, Jadran (Applied Thermal Engineering)
The parameters required to calculate the energy efficiency of household refrigerating appliances (i.e. refrigerators, freezers and their combinations) are determined by standard measurements. According to regulations, these measurements are carried out when the appliances are new. It is known from previous studies that various technical aging mechanisms can increase electrical energy consumption by up to 36 % over a product lifespan of 18 years. In order to determine the time dependence of the energy consumption of household refrigerating appliances, repeated measurements are carried out in this work. Eleven new appliances are examined under standard measurement conditions. After just two years of operation, an additional energy consumption of up to 11 % is determined. Furthermore, 21 older appliances that had previously been measured in new condition are tested again after up to 21 years of operation. For these older appliances, an average increase of energy consumption of 28 % is found. For individual appliances, the maximum increase is 36 %. An aging model is developed on the basis of these measurement results, which may help to predict the aging-related increase of energy consumption of household refrigerating appliances. This model shows an average increase in energy consumption of 27 % for an appliance age of 16 years. Supplemental performance tests of eight compressors do not show any significant aging effects related to these devices after two years of operation. Furthermore, measurements of the thermal conductivity of aged polyurethane foam test samples are carried out and an increase of its thermal conductivity of 26 % over a period of about three years is determined.
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Thermodynamic Properties for 1-Hexene – Measurements and Modeling - Betken, Benjamin; Beckmüller, Robin; Ali Javed, Muhammad; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Experimental study of two cascaded organic Rankine cycles with varying working fluids - Abbas, Wameedh Khider Abbas; Linnemann, Matthias; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management)

Thermodynamic Properties of Methyl Diethanolamine - Neumann, Tobias; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (International Journal of Thermophysics)
Abstract The homogeneous density of the liquid phase is experimentally investigated for methyl diethanolamine. Data are obtained along five isotherms in a temperature range between 300 K and 360 K for pressures up to 95 MPa. Two different apparatuses are used to measure the speed of sound for the temperatures between 322 K and 450 K with a maximum pressure of 95 MPa. These measurements and literature data are used to develop a fundamental equation of state for methyl diethanolamine. The model is formulated in terms of the Helmholtz energy and allows for the calculation of all thermodynamic properties in gaseous, liquid, supercritical, and saturation states. The experimental data are represented within their uncertainties. The physical and extrapolation behavior is validated qualitatively to ensure reasonable calculations outside of the range of validity. Based on the experimental datasets, the equation of state is valid for temperatures from 250 K to 750 K and pressures up to 100 MPa.
Keywords: Condensed Matter Physics

Measurement procedure for acoustic absorption and bulk viscosity of liquids - Claes, Leander; Chatwell, René Spencer; Baumhögger, Elmar; Hetkämper, Tim; Zeipert, Henning; Vrabec, Jadran; Henning, Bernd (Measurement)

Effizienzsteigerung von Haushaltskühlgeräten durch polymergebundene Phasenwechselmaterialien - Sonnenrein, Gerrit

Determining the heat flow through the cabinet walls of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al. (International Journal of Refrigeration)
The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary be- cause current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measure- ment method is developed to determine the k ·A value over time. With this method, the k ·A value of four household refrigerating appliances was determined over an interval of 14 months. The k ·A value increased between 3.6% and 11.5% during this period.

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Morbach, A.; Neukötter, M.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Density and Thermodynamic Speed of Sound of Liquid Vinyl Chloride - Javed, Muhammad Ali; Rüther, Moritz; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Reduction of systematic measurement deviation in acoustic absorption measurement systems - Claes, Leander; Baumhögger, Elmar; Rüther, Torben; Gierse, Jan; Tröster, Thomas; Henning, Bernd (Fortschritte der Akustik - DAGA 2020)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

Age-related efficiency loss of household refrigeration appliances: Development of an approach to measure the degradation of insulation properties - Hueppe, Christian; Geppert, Jasmin; Stamminger, Rainer; Wagner, Hendrik; Hoelscher, Heike; Vrabec, Jadran; Paul, Andreas; Elsner, Andreas; Becker, Wolfgang; Gries, Ulrich; Freiberger, Alfred (Applied Thermal Engineering)
Despite the omnipresence of household refrigeration appliances, there is still a lack of knowledge about their agerelated efficiency loss over time. Past studies provide basic evidence for increasing electricity consumption of cooling appliances with ageing but fail to investigate the associated technical wear. Concentrating on the degradation of the thermal insulation, we first determined the ageing process of sealed samples of polyurethane rigid foam by investigating changes in cell gas composition and thermal conductivity over time. Simultaneously, the main challenge was to develop an approach that investigates the age-related efficiency loss of the insulation without its destruction. This testing procedure is referred to as the Bonn method. The non-destructive Bonn method was applied to varying refrigerator models in a series of successive experiments to evaluate the insulation degradation over time. Subsequently, the physical relationship between the test value of the Bonn method and the heat transfer through the multi-layered compartment walls of domestic refrigeration appliances was established, ultimately characterising the degrading insulation in terms of increasing heat transfer. Our results give substantiated evidence that the efficiency loss of cooling appliances is greatly influenced by insulation degradation over time. The ageing of sealed samples of polyurethane rigid foam indicates a large initial increase of thermal conductivity by 15% within the first year, corresponding to a change in cell gas composition. These results are in line with those of the Bonn method, emphasising an increasing heat flow through the multi-layered compartment walls of domestic refrigerators with ageing. Therewith, the present study is of significance to a wide range of stakeholders and forms the basis for future research.

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Quantification of frequency-dependent absorption phenomena - Claes, Leander; Johannesmann, Sarah; Baumhögger, Elmar; Henning, Bernd (2019 International Congress on Ultrasonics)

Henry’s Law Constant of Noble Gases in Water, Methanol, Ethanol, and Isopropanol by Experiment and Molecular Simulation - Linnemann, Matthias; Nikolaychuk, Pavel Anatolyevich; Muñoz-Muñoz, Y. Mauricio; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Thermodynamic Properties of Dodecamethylpentasiloxane, Tetradecamethylhexasiloxane, and Decamethylcyclopentasiloxane - Thol, Monika; Javed, Muhammad Ali; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran (Industrial & Engineering Chemistry Research)

Thermodynamic Speed of Sound Data for Liquid and Supercritical Alcohols - Javed, Muhammad Ali; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Thermodynamic speed of sound of xenon - Javed, Muhammad Ali; Baumhögger, Elmar; Vrabec, Jadran (The Journal of Chemical Thermodynamics)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Bestimmung von Wärmeverlusten in Haushaltskältegeräten - Paul, Andreas; Moczarski, Lukas; Gieselmann, Mirko; Reineke, Michael; Elsner, Andreas; Baumhögger, Elmar; Sonnenrein, Gerrit; Vrabec, Jadran
Wie jedes technische System unterliegen auch Haushaltskältegeräte einer alterungsbedingten Degeneration, die zu einem Anstieg der Energieaufnahme über die Lebensdauer dieser Geräte führt. Ursache hierfür sind verschiedene Effekte, die in dem vom BMWi geförderten Projekt ALGE untersucht werden. Aus den so gewonnenen Erkenntnissen sollen dann degenerationsbeständigere Haushaltskältegeräte entwickelt werden. Eine wichtige Alterungsursache ist der Anstieg der Wärmeleitfähigkeit des PUR-Schaums der Gehäuseisolierung. Zur Bestimmung dieses Einflusses auf die Energieaufnahme ist die Entwicklung neuer Messmethoden notwendig, die zerstörungsfrei sein und den realen Anwendungsbedingungen möglichst nahekommen sollen. Dazu wurde eine Wärmesenke entwickelt, die den Geräteinnenraum unabhängig vom Kältekreislauf abkühlt. Die Wärmesenke ist als Eiswasserbehälter ausgeführt, sodass die Schmelzenthalpie des Eises die durch die Isolierung in den Geräteinnenraum einfallende Wärme aufnimmt. Durch die Bestimmung der Abtauzeit einer bestimmten Eismenge kann so der alterungsbeeinflusste 𝑘∙𝐴-Wert des Gehäuses von Haushaltskältegeräten bestimmt werden.

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (Chemical Engineering Transactions)

Speed of Sound Measurements and a Fundamental Equation of State for Hydrogen Chloride - Thol, Monika; Dubberke, Frithjof H.; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Speed of Sound Measurements and a Fundamental Equation of State for Hydrogen Chloride - Thol, Monika; Dubberke, Frithjof H.; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Large Scale Thermodynamic Data Generation with Molecular Simulation - Rutkai, Gábor

A Spectral Approach to Acoustic Absorption Measurement - Claes, Leander; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (PROCEEDINGS -- AMA Conferences 2017)

Experimental setup of a cascaded two-stage organic Rankine cycle - Dubberke, Frithjof H.; Linnemann, Matthias; Abbas, Wameedh Khider; Baumhögger, Elmar; Priebe, Klaus-Peter; Roedder, Maximilian; Neef, Matthias; Vrabec, Jadran (Applied Thermal Engineering)

Experimental and Computational Study on the Solubility of Argon in Propan-2-ol at High Temperatures - Nikolaychuk, Pavel Anatolyevich; Linnemann, Matthias; Muñoz-Muñoz, Y. Mauricio; Baumhögger, Elmar; Vrabec, Jadran (Chemistry Letters)

Thermophysical properties from experimental speed of sound measurements for working fluids in organic Rankine cycles - Dubberke, Frithjof

Molekulare Simulation als effizientes Werkzeug zur Bestimmung thermodynamischer Stoffdaten - Köster, Andreas

Modeling and simulation of metallic, particle-damped spheres for lightweight materials - Steinle, Tobias
Lightweight materials play an ever growing role in today's world. Saving on the mass of a machine will usually translate into a lower energy consumption. However, lightweight applications are prone to develop performance problems due to vibration induced by the operation of the machine. The Fraunhofer Institute for Manufacturing Technology and Advanced Materials in Dresden conducts research into the damping properties of composite materials. They are experimenting with hollow, particle filled spheres embedded in the lightweight material. Such a system is the technical motivation of this thesis. Ultimately, a numerical experiment to derive the coefficient of restitution is required. The simulation developed in this thesis is based on a discrete element method to track the individual particle and sphere trajectories. Based on a potential based approach for the particle interactions deployed in molecular dynamics, the behavior of the particles can be controlled effectively. The simulated volume is using reflecting boundaries and encloses the hollow sphere. In this work, a highly flexible memory structure was used with a linked cell approach to cope with the highly flexible mass of particles. This allows for a linear complexity of the method in regard to the particle number by reducing the computational overhead of the interaction computation. Multiple numerical experiments show the great effect the particles have on the damping behavior of the system.

Experimental study of phase change materials for photovoltaic modules: Energy performance and economic yield for the EPEX spot market - Japs, Ewald; Sonnenrein, Gerrit; Krauter, Stefan; Vrabec, Jadran (Solar Energy)

Speed of Sound of Oxygen in Supercritical States up to 500 K and 100 MPa - Dubberke, Frithjof H.; Riepold, Markus; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Molecular modeling and simulation for industrial applications - Miroshnichenko, Svetlana

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Fieback, K.; Morbach, A.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Burst design and signal processing for the speed of sound measurement of fluids with the pulse-echo technique - Dubberke, Frithjof H.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Fieback, K.; Morbach, A.; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
This study presents the results of an experimental investigation of the influence of latent thermal heat storage elements on the power consumption as well as the temperature distribution of commercial household refrigerators.Two evaporator types and a standard wireand- tube condenser are equipped with copolymer-bound phase change materials (PCM) and the performance is determined under standard conditions. The results show that refrigerating appliances equipped with PCM can be optimized through modifications of the control strategy to achieve different targets: (a) Power consumption can be significantly reduced by increasing the evaporator and decreasing the condenser temperature. (b) Temperature fluctuations in the refrigerator’s fresh-food compartment during the cooling cycle can be reduced from 4 °C to 0.5 °C. (c) The cooling cycle duration can be tripled without compromising the fresh-food compartment conditions. The latter may help to meet the growing demand for balancing power consumption to stabilize the power grid, e.g. if the share of highly fluctuating, sustainable energy supply is large.

Numerical Simulation of the Damping Behavior of Particle-Filled Hollow Spheres - Steinle, Tobias; Vrabec, Jadran; Walther, Andrea (Proc. Modeling, Simulation and Optimization of Complex Processes (HPSC))
In light of an increasing awareness of environmental challenges, extensive research is underway to develop new light-weight materials. A problem arising with these materials is their increased response to vibration. This can be solved using a new composite material that contains embedded hollow spheres that are partially filled with particles. Progress on the adaptation of molecular dynamics towards a particle-based numerical simulation of this material is reported. This includes the treatment of specific boundary conditions and the adaption of the force computation. First results are presented that showcase the damping properties of such particle-filled spheres in a bouncing experiment.

Reducing the power consumption of household refrigerators through the integration of latent heat storage elements in wire-and-tube condensers - Sonnenrein, G.; Elsner, A.; Baumhögger, Elmar; Morbach, A.; Fieback, K.; Vrabec, J. (International Journal of Refrigeration)

Apparatus for the measurement of the speed of sound of ammonia up to high temperatures and pressures - Dubberke, Frithjof H.; Rasche, David B.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Prediction methods for pool boiling heat transfer: A state-of-the-art review - Gorenflo, Dieter; Baumhögger, Elmar; Herres, Gerhard; Kotthoff, Stephan (International Journal of Refrigeration)

Zum Einfluss von Fluid- und Heizflächeneigenschaften auf Wärmeübergang und Blasenbildung beim Sieden - Kotthoff, Stephan

Vapor-liquid equilibrium properties from molecular simulation and experiment - Windmann, Thorsten

Zunahme des Stromverbrauchs von Haushaltskältegeräten durch Alterung - Elsner, Andreas; Müller, Michael; Paul, Andreas; Vrabec, Jadran

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part II: Circumferential variation of the wall superheat for a horizontal 25mm copper cylinder - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part I: Integral heat transfer for horizontal copper cylinders - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

An apparatus for the determination of speeds of sound in fluids - Gedanitz, Holger; Dávila, María J.; Baumhögger, Elmar; Span, Roland (The Journal of Chemical Thermodynamics)

POOL BOILING IN HIGHLY VISCOUS MIXTURES - DESIGN OF A NEW APPARATUS AND RESULTS OF PRETESTS - Span, R.; Gerber, M.; Buljina, I.; Baumhögger, Elmar (Boiling)

3-DIMENSIONAL DESCRIPTION OF THE MICROSTRUCTURE OF HEATED SURFACES IN NUCLEATE POOL BOILING - Luke, Andrea; Baumhögger, Elmar; Scheunemann, P. (Multiphase Science and Technology)